2023
DOI: 10.1093/cid/ciad201
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of Hepatitis B Virus (HBV) Vaccine With a Toll-Like Receptor 9 Agonist Adjuvant in HBV Vaccine-Naïve People With Human Immunodeficiency Virus

Abstract: In this international, multicenter open-label study (ACTG A5379) of HepB-CpG vaccine in people with HIV without prior Hepatitis B Virus (HBV) vaccination, all 68 participants achieved HBV seroprotective titers after the 3-dose series in the primary analysis. No unexpected safety issues were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The AIDS Clinical Trials Group 5379 clinical trial of 3 doses of the CpG-adjuvanted recombinant hepatitis B vaccine at 0, 1, and 6 months among 68 PWH recently reported that, after 3 doses in the vaccine-naive group, 100% of participants achieved seroprotective anti-HBs titers, and 98.5% achieved seroprotective titers after 2 doses when titers were checked 6 months before administration of the third dose [ 30 ]. While higher anti-HBs titers are substantially lower after 2 doses than after 3 doses, if patients complete 2 doses and do not complete the third, they are more likely to have protection against HBV infection than with the current alum-adjuvanted HBV vaccine strategies, with either standard or double-dose vaccines [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AIDS Clinical Trials Group 5379 clinical trial of 3 doses of the CpG-adjuvanted recombinant hepatitis B vaccine at 0, 1, and 6 months among 68 PWH recently reported that, after 3 doses in the vaccine-naive group, 100% of participants achieved seroprotective anti-HBs titers, and 98.5% achieved seroprotective titers after 2 doses when titers were checked 6 months before administration of the third dose [ 30 ]. While higher anti-HBs titers are substantially lower after 2 doses than after 3 doses, if patients complete 2 doses and do not complete the third, they are more likely to have protection against HBV infection than with the current alum-adjuvanted HBV vaccine strategies, with either standard or double-dose vaccines [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heplisav‐B is a new hepatitis B virus vaccine with an immunostimulatory adjuvant. It has been examined as 3 doses in PLWH without prior HBV vaccination showing 95% efficacy after 2 doses and 100% efficacy after 3 doses 8 . During the past decade considerable progress in HBV infection control have been achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The other more promising approach is to use HepB-CpG for the primary vaccine series. Among 68 HIV-positive individuals, 100% achieved seroprotection 4 weeks after the vaccine series; of these, 88% had anti-HBs levels > 1000 mIU/mL [104]. In another retrospective analysis, HepB-CpG was associated with a significantly higher rate of seroprotection compared with HepB-alum-based hepatitis B vaccines, 93.4% compared with 57.6%, respectively [105].…”
Section: Human Immunodeficiency Virusmentioning
confidence: 96%